Integrating 21st-century skills in English material development: What do college students really need? - Menggo, Sebastianus; Ndiung, Sabina; Midun, Hendrikus (Universitas Islam Negeri Banda Aceh, 2022)
The 21st-century education emphasizes a number of indicators that teachers, students, parents, and other education stakeholders should completely understand. English teachers should be encouraged to be able to integrate the intended 21st-century competency indicators into instructional materials that are preceded by a needs analysis stage. Needs analysis is crucial in designing English materials as it serves as a valuable tool for practitioners to create English materials aligned with students' target and learning needs. As a consequence, needs analysis is seen as a necessary component of the teaching practice. The purposes of this study are to examine and reveal the numerous types of students' target needs and learning needs for English material development. This study examined two English lecturers and 206 students enrolled in the primary education department. The data collection instrument was a questionnaire and the data were analyzed using a software program, namely an excel chart data series. Findings indicated that the students' target needs included necessities, lacks, and wants, whereas learning needs included input, procedure, setting, learner's role, and lecturer's role in the teaching-learning process. Students' target and learning needs emphasized the importance of developing English materials that boosted 21st-century education skills. English materials should be adjusted to meet the needs of students' future careers, with a particular emphasis on the eleven sub-skills of 21st-century education.